1957
DOI: 10.1085/jgp.40.5.683
|View full text |Cite
|
Sign up to set email alerts
|

Maintained Activity in the Cat's Retina in Light and Darkness

Abstract: Nervous activity has been recorded from the unopened eye of decerebrate cats. Recordings were made with metal electrodes or with small micropipettes from ganglion cells or nerve fibers. Continuous maintained discharges were seen in all ganglion cells during steady illumination of their receptive fields, as well as in complete darkness. Possible artefacts, such as electrode pressure, abnormal circulation, anesthetic, and several other factors have been excluded as the source of the maintained dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
1

Year Published

1963
1963
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(139 citation statements)
references
References 18 publications
9
129
1
Order By: Relevance
“…The oldest report that is known to the authors is in the activity of motoneurons in humans (Hagiwara 1949). Subsequent studies have found nonrenewal spiking statistics in retinal cat retinal ganglion cells (Kuffler et al 1957;Rodieck 1967;Levine 1980), cat superior olivary neurons (Goldberg et al 1964;Tsuchitani and Johnson 1985), cat peripheral auditory fibers (Lowen and Teich 1992), cat cochlear nuclear neurons (Goldberg and Greenwood 1966), cat medullary sympathetic neurons (Lewis et al 2001), cat sympathetic efferent fibers (Floyd et al 1982), pigeon vestibular afferents (Correia and Landolt 1977), weakly electric fish electroreceptor neurons (Longtin and Racicot 1997;Chacron et al 2000;Ratnam and Nelson 2000;Chacron et al 2001b;Chacron et al 2005b;Gussin et al 2007), paddlefish electroreceptors (Bahar et al 2001;Neiman and Russell 2001;Neiman and Russell 2004), catfish electroreceptors (Schäfer et al 1995), weakly electric fish electrosensory pyramidal neurons (Doiron et al 2003;Chacron et al 2007), honeybee mushroom body neurons (Farkhooi et al 2009), grasshopper auditory neurons (Schwalger et al 2010), primate spinothalamic neurons (Surmeier et al 1989), rat mesencephalic reticular neurons (Lansky and Radil 1987), primate somatosensory cortical neurons (Yamamoto and Nakahama 1983;Lebedev and Nelson 1996;Nawrot et al 2007), as well as rat entorhinal cortical pyramidal and interneurons (Engel et al 2008). We note that the last five studies challenge the notion that cortical neurons can be described by a renewal process such as the Poisson process and shall return to this point later.…”
Section: Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The oldest report that is known to the authors is in the activity of motoneurons in humans (Hagiwara 1949). Subsequent studies have found nonrenewal spiking statistics in retinal cat retinal ganglion cells (Kuffler et al 1957;Rodieck 1967;Levine 1980), cat superior olivary neurons (Goldberg et al 1964;Tsuchitani and Johnson 1985), cat peripheral auditory fibers (Lowen and Teich 1992), cat cochlear nuclear neurons (Goldberg and Greenwood 1966), cat medullary sympathetic neurons (Lewis et al 2001), cat sympathetic efferent fibers (Floyd et al 1982), pigeon vestibular afferents (Correia and Landolt 1977), weakly electric fish electroreceptor neurons (Longtin and Racicot 1997;Chacron et al 2000;Ratnam and Nelson 2000;Chacron et al 2001b;Chacron et al 2005b;Gussin et al 2007), paddlefish electroreceptors (Bahar et al 2001;Neiman and Russell 2001;Neiman and Russell 2004), catfish electroreceptors (Schäfer et al 1995), weakly electric fish electrosensory pyramidal neurons (Doiron et al 2003;Chacron et al 2007), honeybee mushroom body neurons (Farkhooi et al 2009), grasshopper auditory neurons (Schwalger et al 2010), primate spinothalamic neurons (Surmeier et al 1989), rat mesencephalic reticular neurons (Lansky and Radil 1987), primate somatosensory cortical neurons (Yamamoto and Nakahama 1983;Lebedev and Nelson 1996;Nawrot et al 2007), as well as rat entorhinal cortical pyramidal and interneurons (Engel et al 2008). We note that the last five studies challenge the notion that cortical neurons can be described by a renewal process such as the Poisson process and shall return to this point later.…”
Section: Overviewmentioning
confidence: 98%
“…Several investigators have reported nonrenewal spike train statistics in the form of a negative ISI serial correlation coefficient at lag 1 that is significantly different from zero (Kuffler et al 1957;Goldberg et al 1964;Yamamoto and Nakahama 1983;Tsuchitani and Johnson 1985;Schäfer et al 1995;Chacron et al 2000;Chacron et al 2007;Nawrot et al 2007;Engel et al 2008;Farkhooi et al 2009). As mentioned above, this implies that ISIs that are shorter than average tend to be followed by ISIs that are longer than average and vice versa, thus giving rise to patterning in the spike train.…”
Section: Negative Interspike Interval Correlations At Lagmentioning
confidence: 99%
“…Finally, the rescaled distribution of inter-spike intervals from the experiment can be fitted by a homogeneous Gamma distribution (2) with fixed rate λ = 1 [KFB57]. The shape parameter k is determined from the moments (meanτ and variance σ 2 τ ) of the empirical rescaled ISI distribution as:…”
Section: Modeling Spike Trains With Stimulus-dependent Rate Modulationmentioning
confidence: 99%
“…Interval distributions of experimentally observed spike trains often exhibit dependencies on prior activity and are thus nonrenewal (Kuffler et al, 1957;Werner and Mountcastle, 1963;Teich et al, 1990;L owen and Teich, 1992). Surrogate spike trains that preserved dependencies between adjacent ISIs were constructed from the afferent data.…”
Section: Binomiall Y Generated Spik E Train (B)mentioning
confidence: 99%